The Results of the Planned Relaparotomy and Laparostomy in Treatment of Generalized Purulent Peritonitis - Yaroslav M. Leshchishin; Ildar G. Mugatasimov; Andrey I. Baranov; Konstantin V. Potekhin; Sergey A. Yaroshchuk (Acta Biomedica Scientifica)
Background. Laparostomy (open abdomen) is an aggressive surgical treatment of peritonitis and it requires justification of its effectiveness. Aims. The aim of the study was to determine the effectiveness of laparostomy and planned rehabilitation in patients with common purulent peritonitis.Materials and methods. Retrospective analysis of the results of laparostomy and planned sanations in patients with common purulent peritonitis. The study included 101 case histories. Inclusion criteria: generalized purulent peritonitis established in the primary surgical intervention that required the implementation of laparotomy. The excluded from the study were immunocompromised patients, hemodialysis patients, patients with pancreatic necrosis, closed abdominal trauma, class C liver cirrhosis, carcinomatosis, cancer cachexia, disseminated tuberculosis, total mesenteric thrombosis. In statistic processing we used indicators of median and inter quartile ranges, methods of nonparametric statistics (Mann – Whitney criterion). The level of significance was α = 0.05.Results. The whole group is divided into three subgroups according to MPI: subgroup I – 20 people, subgroup II – 57, subgroup III – 24. The method of planned sanation of the abdominal cavity in combination with laparostomy was applied in 34 cases (33.6 %). In the first subgroup in two cases (10 %), in the second – in 18 (31.6 %), in the third – 14 (58.3 %). The deceased, regardless of the chosen surgical technique, were characterized by higher values of integral scales. The severity of the condition of the surviving patients in which the technique was used at the time of admission was significantly higher than the severity of the surviving patients, in which laparostomy SAPS II was not used (p = 0.4716). However, their age was significantly older (p = 0.5476). The deceased patients were older 60 years with high rates on the above mentioned integrated scales.Conclusions. The results showed that patients older than 60 years, II & III on MPI and with high values of integral scales require more balanced and differential approach when using laparostomy (open abdomen).